Staphylococcus spp. in the etiology of peritonitis in peritoneal dialysis: Risk factors of the host and microorganism - Santos, Ana Cláudia Moro Lima dos [UNESP]; de Lourdes Ribeiro de Souza da Cunha, Maria [UNESP] (My University, 2021)
Bacterial peritonitis remains a major complication of peritoneal dialysis (PD), often leading to the interruption of the technique and an important impact on mortality. When such episodes are serious and long, they may lead to lesion of the peritoneal membrane. Therefore, PD professionals highlight the prevention and treatment of these infections aiming at a quick resolution, which contributes to the preservation of the peritoneal membrane function. The clinical presentation and progression of the episode of peritonitis are significantly influenced by characteristics of the causative agent. PD peritonitis is in most cases caused by Gram-positive cocci - Staphylococcus spp. - including the species of Coagulase-negative staphylococci (CoNS) and S. aureus. The CoNS group comprises more than 50 species, and some of them are already well established as causes of PD-related peritonitis, especially S. epidermidis. In general, peritonitis caused by CoNS shows a light clinical course and has a high rate of resolution, but recurrent infections that had apparently been cured are observed. S. aureus is associated with: more severe episodes, a worse overall prognosis compared to other peritonitis, a higher risk of hospitalization, catheter removal, and death, while these patients are significantly more likely to switch to hemodialysis. The severity of S. aureus infections is associated with virulence factors produced by these bacteria, such as enzymes and several toxins with various activities including those which damage cell membranes and which function as superantigens. Another important virulence factor for the occurrence of peritonitis is biofilm production by S. aureus and mainly by CoNS, which facilitates bacterial adhesion to catheters and colonization of the infection site, and protects the bacterial cells from natural defense mechanisms and from antibiotic action. The treatment of these infections can also be unsuccessful due to the presence of resistance genes that these microorganisms may have, i.e., the presence of mecA gene that causes methicillin resistance. This gene is located in a mobile genetic element called staphylococcal cassette chromosome mec (SCCmec) which allows transmission of the resistance characteristic with important implications as it results in limiting the use of - lactam antibiotics. One of the contributing factors for infections caused by S. aureus is the fact that PD patients are more likely to be nasal carriers of S. aureus when compared to the healthy population, and then it is an important risk factor for infections. Studies using typing methods have shown that the nasal isolate from the carrier and the strain causing the peritonitis are often indistinguishable. Thus, there has been a significant decrease in the rates of infections by S. aureus in recent years with the use of topical antibiotics for decolonization, especially mupirocin. Therefore, this chapter aims at addressing issues related to PD peritonitis caused by Staphylococcus spp. highlighting the epidemiology and risk factors of the host and microorganism when these infections occur.